Ink-Jet Printing and Electrodeposition for the Production of Free Standing and Polymer Supported Micronet Electrodes. (1st January 2015) - Oriani, A. V.; Spreafico, M. A.; Pedroli, F.; Marrani, A.; Falco, I.; Cojocaru, P.; Triulzi, F.; Apostolo, M.; Magagnin, L.
Abstract : A study on optimization of Ink-Jet printing parameters, in terms of drop spacing, operative voltage and waveform, metallic line width and spacing is presented, with the aim of producing flexible Transparent Conducting Electrodes (TCEs). Silver micronets were produced by Ink-Jet printing on PET films, to obtain polymer supported transparent electrodes; preliminary studies were also performed on the production of freestanding electrodes, by electrodeposition on the printed micronets. The study reveals that PET supported transparent conductive electrodes can be obtained by ink-jet printing, having improved performances with respect to Indium Tin Oxide (ITO) in terms of resistivity and resistance to bending: no cracking or delamination was observed during bending of the micronets and resistance, measured between two points at 3 cm distance, is one order of magnitude lower for the micronets. Preliminary studies on production of freestanding meshes reveal that this process is promising and allows further reduction in electrode resistance, measured between two points at 3 cm distance, of one order of magnitude. Line width, which is the main limitation of this process, can be conformally reduced by electropolishing without causing collapse of the freestanding micronet.